Jim Arnosky's all about manatees. - Arnosky, Jim. (New York : Scholastic Nonfiction, 2008)
Illustrations and simple text introduce young readers to the physical characteristics, habits, and habitats of manatees.
Booklist.
Kirkus Review.
School Library Journal.
3.1
K-3
Keywords: Manatees -- Juvenile literature; Manatees; Manatees